Dietary supplementation of N‐carbamylglutamate and effects on growth, intestinal enzyme activities, immunological and antioxidant abilities of juvenile yellow catfish (Pelteobagrus fulvidraco). (19th June 2019) - Zhao, Hongxia; Qiao, Guoxian; Cao, Junming; Huang, Yanhua; Wang, Guoxia; Chen, Bing; Chen, Xiaoying; Mo, Wenyan
Abstract: The effects of N‐carbamylglutamate (NCG) on growth, intestinal enzyme activities, immunological and antioxidant parameters were evaluated by a 56‐d feeding trial in Pelteobagrus fulvidraco fed diets containing NCG with 0, 250, 500, 1, 000 or 2, 000 mg/kg, respectively. The results showed that 250 mg/kg of NCG resulted in significantly higher weight gain, intestine fold height, intestine lipase, serum lysozyme, glutathione peroxidase and total antioxidant capacity than control ( p <  0.05). However, higher intestine trypsin, arginase, arginine decarboxylase, ornithine decarboxylase, diamine oxidase activities and serum nitric oxide content were observed in 500 mg/kg NCG group compared to control or 2, 000 mg/kg ( p <  0.05). The survival rate, intestine muscular layer thickness, serum lysozyme and superoxide dismutase activities in 2, 000 mg/kg NCG group were significantly lower than those in control and 250 mg/kg group, accompanied by the higher feed conversion ratio in the same group ( p <  0.05). Together, dietary NCG level at 250 or 500 mg/kg improved growth, intestinal enzyme activities, immunological and antioxidant abilities, while high NCG level of 2, 000 mg/kg had a negative effect. Quadratic regression analysis on weigh growth, diamine oxidase and lysozyme activities indicated that the recommended optimum dietary NCG level was 213.48–314.50 mg/kg of the dry diet.